2022
DOI: 10.1093/humrep/deac094
|View full text |Cite
|
Sign up to set email alerts
|

The healthy female microbiome across body sites: effect of hormonal contraceptives and the menstrual cycle

Abstract: STUDY QUESTION How does hormonal contraceptive use and menstrual cycle phase affect the female microbiome across different body sites? SUMMARY ANSWER The menstrual cycle phase, but not hormonal contraceptive use, is associated with the vaginal and oral but not the gut microbiome composition in healthy young women. WHAT IS KNOWN ALREADY Women with low vaginal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 74 publications
2
37
0
Order By: Relevance
“…These studies have shown that the pregnant vaginome is less rich and less diverse as compared to the non-pregnant vaginome, with a high proportion of Lactobacillus spp. [ 53 , 54 ]. Important factors such as behavioral changes, physio-chemical changes in the mucosa, hormonal changes leading to immune modulation, and changes in the genital tract may define the modulation in structure and function of the vaginome, making it unique from non-pregnant females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have shown that the pregnant vaginome is less rich and less diverse as compared to the non-pregnant vaginome, with a high proportion of Lactobacillus spp. [ 53 , 54 ]. Important factors such as behavioral changes, physio-chemical changes in the mucosa, hormonal changes leading to immune modulation, and changes in the genital tract may define the modulation in structure and function of the vaginome, making it unique from non-pregnant females.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence demonstrating the associations between vaginome dysbiosis and preterm birth. Vaginome dysbiosis is caused mainly by bacterial vaginosis, where Firmicutes and Actinobacteria phyla were identified as causative bacteria [ 13 , 14 , 16 , 54 ]. Bacterial vaginosis in early pregnancy is linked to preterm or delivery of a low birthweight infant [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies investigating the relationship between menstruation and other human microbiomes have been performed. A study reports a lack of significant menstruation-driven changes in the saliva and fecal microbiomes, yet discloses an increased diversity in the vaginal microbiome during menses, which is ensured by an expansion of Lactobacillus during the follicular and luteal phases [ 90 ]. Similarly, another recent study reports increased vaginal microbial diversity and a correlation between Lactobacillus abundances and predicted estradiol levels across the menstrual cycle [ 91 ].…”
Section: Changes In Gut Microbiome During the Menstrual Cyclementioning
confidence: 99%
“…64 65 67 70 Data analyses Extraction and sequencing of microbial DNA DNA extraction will be performed with standardised and automated pipelines as previously optimised by our group for vaginal, 71 saliva 72 and faecal samples. 73 The extraction method allows for the detection of all domains of life, namely bacteria, archaea, small eukaryotes including fungi and viruses. Longitudinal profiling of vaginal, faecal and oral microbiome samples will be performed at the Centre for Translational Microbiome Research (CTMR), Karolinska Institutet, Sweden, with a focus on microbial diversity and the correlation between the relative abundances of taxonomic groups with external factors.…”
Section: Registry Datamentioning
confidence: 99%
“…DNA extraction will be performed with standardised and automated pipelines as previously optimised by our group for vaginal,71 saliva72 and faecal samples 73. The extraction method allows for the detection of all domains of life, namely bacteria, archaea, small eukaryotes including fungi and viruses.…”
Section: Cohort Descriptionmentioning
confidence: 99%